Recruitment in small japanese company - Jarošová, Ilona; Dvořáková, Zuzana, 1960-; Jindřich, Tomáš, 1980-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2008)
The thesis focuses on employee recruitment in japanese environment. Among others, the discussed topics include interview process, experiences of recruitment agences with japanese companies on the Czech market and recommendations of specific steps for the analysed company. The hypothesis of the thesis is that japanese compnanies are unsuccessful regarding employee recruitment in the Czech Republic, suffer from insufficient interest of potencial candidates . All these factors combined with general underestimating of HR policies lead to high employee fluctuation in japanese branch offices.
Vedoucí práce: Zuzana Dvořáková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2008
Rok obhajoby 2008
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses